Valuation of the viceroyalty-republican military patrimony of Metropolitan Lima. Study case: Barbones Barracks, Lima-Peru, 2020 - Hayakawa, José; Celis Estrada, Diego; Jara Boza, Yonatan (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
The military heritage built in the regions of Peru is conspicuously invisible. The present investigation contributes to its patrimonial valuation. It has a qualitative approach and an exploratory level. For the recording, photogrammetric means of collecting metric information were used (Agisoft Metashape Professional software, professional/semi-professional camera equipment, a DJI Mavic Pro drone, and desktop computers). In the historical study, the technique used was to review secondary sources, maps and photographs of the total history of the property, and then explore documents from the 19th century in the archive. One notable result is that, in relation to the overarching goal of deepening the precise architectural record of “Fort Barbones,” the process undertaken— even amidst the Covid-19 pandemic—has been both possible and valuable. It has transformed problems into opportunities for cooperative, technological, and innovative work.